Programa Proinfância: considerações sobre os efeitos nas Políticas Municipais de Educação Infantil - Sandro Coelho Costa (2015)
This research investigated the expansion of early childhood education policies in Brazil through the National Restructuring and Equipment Acquisition for Public School Network Early Childhood Education Program - Proinfância. The federal program proposes restructuring and construction of the physical network of early childhood education units in the country, for the whole age group 0-5 years. Data sources were composed of interviews with the Ministry of Education, the Municipal Education Departments of three municipalities in the metropolitan region of Belo Horizonte - MRBH and the direction and coordination of Early Childhood Institutions in operation, resulting from the program. In addition, they raised the normative documents and concerning federal, state and municipal. For this analysis were performed cotejamentos between references and studies of the regulation of public policies and also of the issues surrounding the federal relations in Brazil. Working assumptions developed by the authors following were used: Barroso (2003; 2004; 2005; 2006, 2006a), Dupriez. and Maroy (2000); Afonso (2010); And Duarte Oliveira, (2005); Hypolito, (2010); Maroy, (2011). Seeking to understand the complex relationships involving the loved national federated in the implementation of basic education in Brazil was carried out a history of the federal pact and the political implications of this agreement in offering educational units (ABRUCIO And FRANZESE, 1998; ABRUCIO, 1998; Cury, 2010 ). It is shown that public policies require effective coordination between federal agencies and more explicit mechanisms governing this joint. So even being a large nation-wide initiative, involving investment of relevant financial resources, Proinfância needs additional technical contributions at the municipal level for the early childhood education policy to respond satisfactorily to the demand and the status of the obligation, quantitatively and qualitatively . Highlight the uniqueness of the actions in the area and the volume of financial resources, in 2014 3.5 billion, directed to this stage of basic education. The program, the DCNEI and documentation on quality COEDI / MEC have fulfilled the role of spreading in the country assumptions for the organization of the National Early Childhood Education policy.